Strategic Registration of Voters: the Chilean Case - Giacomo De Luca (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
In this paper we have investigated how the employment relationship, if it implies transfer of rents, may allow employers to control the voting behavior of their workers and lead to a strategic registration of voters. This is feasible when individual voting behavior is observable, as in open ballot elections. More easily controlled voters are more likely registered providing an even larger impact of vote controlling on election results. Making individual vote truly secret (for instance with the adoption of a secret ballot) significantly reduces this control. Moreover, we show that as long as electoral districts are heterogeneous enough, i.e. contain also free voters, any attempt to control votes on the basis of district aggregate results is bound to fail. We test the predictions of the model by examining in detail the effects of the introduction of the secret ballot in Chile in 1958.
Keywords: D72; D82; J41; K39; 330